The Autophagic Machinery in Viral Exocytosis - Münz, Christian (Frontiers in Microbiology, 2017)
The discovery of the molecular machinery of autophagy, namely Atg proteins, was awarded with the Nobel prize in physiology and medicine to Yoshinori Ohsumi in 2016. While this machinery was originally identified by its ability to allow cells to survive starvation via lysosomal degradation to recycle cellular components, it has recently become apparent that it also is used by cells to secrete cytoplasmic constituents. Furthermore, viruses have learned to use this Atg supported exocytosis to exit cells, acquire envelopes in the cytosol and select lipids into their surrounding membranes that might allow for increased robustness of their virions and altered infection behavior. Along these lines, picornaviruses exit infected cells in packages wrapped into autophagic membranes, herpesviruses recruit autophagic membranes into their envelopes and para- as well as orthomyxoviruses redirect autophagic membranes to the cell membrane, which increases the robustness of their envelope that they acquire at this site. These recent findings open a new exciting field on the regulation of degradation versus release of autophagic membranes and will be discussed in this minireview.